Conscientious marketing: making a difference in people’s lives - Quraeshi, Zahir A.; Luqmani, Mushtaq; Schultz, Roberta J.; Zain, Osman M. (Business Perspectives, 2010)
The fundamental marketing practices, that have driven the teaching and practice of marketing, have evolved from their early beginnings to today, where societal marketing has been advanced as a concept that should drive marketing practices. There is, under contemporary circumstances, a need to reexamine the fundamental concepts on which present marketing initiatives are based. An innovative approach, that we refer to as conscientious marketing (CM), proposes a shift in businesses towards primarily emphasizing societal goals rather than economic objectives. The authors distinguish CM from societal marketing, and advocate the adoption of CM by businesses,particularly in the developing countries, where there are urgent societal needs.We suggest marketing mix initiatives that should be explored for application under the umbrella of CM in serving the poor in the developing world.